Soledades de seis poetas suecos - Lagerkvist, Pär 1891-1974; Gullberg, Hjalmar 1898-1961; Boy, Karin; Lundlkvist, Artur 1906-1991; Ekelof, Gunnar 1907-1968; Lindegren, Erik 1910-1968
Contiene: Pär Lagerkvist, Hjalmar Gullberg, Karin Boye, Artur Lundkvist, Gunnar Ekelöf, Erik Lindegren